Tumor Customized 2D Supramolecular Nanodiscs for Ultralong Tumor Retention and Precise Photothermal Therapy of Highly Heterogeneous Cancers. Issue 21 (8th April 2022) - Lin, Peng; Xue, Yucheng; Mu, Xueluer; Shao, Youyou; Lu, Qian; Jin, Xiangang; Yinwang, Eloy; Zhang, Zengjie; Zhou, Hao; Teng, Wangsiyuan; Sun, Hangxiang; Chen, Weida; et al.
Abstract: Target therapy for highly heterogeneous cancers represents a major clinical challenge due to the lack of recurrent therapeutic targets identified in these tumors. Herein, the authors report a tumor‐customized targeting photothermal therapy (PTT) strategy for highly heterogeneous cancers, by which 2D supramolecular self‐assembled nanodiscs are modified with tumor‐specific binding peptides identified by phage display techniques. Taking osteosarcoma (OS) as a model heterogeneous cancer, an OS targeting peptide (OTP) is first selected after biopanning and is demonstrated to successfully bind to this heterogeneous cancer cells/tissues. Successful conjugation of OTP to heptamethine cyanine (Cy7)‐based 2D nanodiscs Cy7‐TCF (2‐dicyanomethylene‐3‐cyano‐4, 5, 5‐trimethyl‐2, 5‐dihydrofuran, TCF) enables the 2D nanodiscs to specifically target the heterogeneous tumor. Notably, a single dose injection of this targeted nanodisc (T‐ND) not only effectively induces enhanced photothermal tumor ablation under near‐infrared light, but also exhibits sevenfold increase of tumor retention time (more than 24 days) compared to generic nanomedicine. Thus, the authors' findings suggest that the combination of phage display‐based affinity peptides selection and 2D supramolecular nanodiscs leads to the development of a platform technology for highly heterogeneous cancers precise therapy, offering specific tumor targeting, ultralong tumor retention, and precise PTT. Abstract : This study introduces a strategy for highly heterogeneous cancers precision medicine by a tumor‐customized 2D supramolecular nanodisc (targeted nanodiscs (T‐ND)), synthesized by modifying Cy7‐TCF crystal with tumor‐specific binding peptides identified by phage display biopanning. T‐ND shows excellent photothermal efficacy to ablate the tumors by the precise delivery to tumors, and achieves ultralong tumor retention time of more than 24 days.